„Od świtu do zmierzchu” – współczesne obrazy miasta w projektach dokumentalnych Maciej Drygasa i Mirosława Dembińskiego - Mąka-Malatyńska, Katarzyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
“The World from Dawn til Dask”. Contemporary Images of the City in the Documentary Projects of Maciej Drygas and Mirosław Dembiński The text refers to two documentary projects that were created by well-known Polish documentary film directors: Maciej Drygas and Mirosław Dembiński. The first one, Łódź from Dawn till Dusk, was made as a part of the education program at the Polish National Film, Television and Theatre School in Łódź in 2007. For several years, students in the second year of the Directing Department made short films about Łódź, forming out of this mosaic, images of the city from dawn till dusk. After having been experienced in Łódź, the project led to the idea of using this method to describe various cities around the world. Finally, five films were made in five different cities under the auspices of the Adam Mickiewicz Institute. This article concentrates on the analysis of the structure of these films and the images of the cities that emerge out of them.